Catalytic Deuterium Incorporation within Metabolically Stable β-Amino C─H Bonds of Drug Molecules - Chang, Yejin (J Am Chem Soc, 2019)
An efficient deuteration process of β-amino C─H bonds in various N-alkylamine-based pharmaceutical compounds has been developed. Catalytic reactions begin with the action of Lewis acidic B(C(6)F(5))(3) and Brønsted basic N-alkylamine, converting a drug molecule into the corresponding enamine. The acid/base catalysts also promote the dedeuteration of acetone-d(6) to afford a deuterated ammonium ion. Ensuing deuteration of the enamine then leads to the formation of β-deuterated bioactive amines with up to 99% deuterium incorporation.